Effects of extended reality on language learning: A meta-analysis - Chen, Jingying; Dai, Jian; Zhu, Keke; Xu, Liujie (Frontiers in Psychology, 2022)
In recent years, there has been increasing use of extended reality (XR) in language learning. Many scholars have conducted empirical research on the relationship between the two, but conclusions have been inconsistent, which calls for an organization and reanalysis of relevant literature. Articles published between 2000 and 2022 on the impact of XR on language learning were retrieved from the Web of Science and Scopus databases, and 17 of them (including 21 independent samples and 993 subjects) were included in this meta-analysis. The findings indicate that XR could promote language learning (effect size = 0.825). The moderating effects of education level, target language, and technology type were also tested, and the results indicate that the target language type significantly moderated the effect of XR technology on language learning (Q = 30.563, p < 0.001). Moreover, based on the subgroup analysis, several research questions worthy of further exploration in this field are discussed. Some suggestions are provided, noting that these technologies should be personally designed for learners and learning objects when applied in order to improve the effects of language learning.